Domy korekcyjne dla duchowieństwa diecezjalnego na ziemiach polskich w XIX wieku z uwzględnieniem Galicji i klasztoru karmelitów bosych w Zagórzu - Nabywaniec, Stanisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
W niniejszym artykule przedstawiono kwestię przywrócenia karności duchowieństwa diecezjalnego w Galicji na przykładzie domu korekcyjnego w Zagórzu, w kontekście pozostałych ziem polskich w zaborze pruskim i rosyjskim oraz na terenach monarchii habsburskiej, jak też podległych im korekcyjnym instytucjom kościelnym. Zagadnienie to ukazano na tle obowiązującego józefińskiego i postjózefińskiego systemu utrzymania i przywracania karności osób duchownych nie tylko w zakresie postaw moralnych, ale także jako formy przywoływania niepokornych politycznie duchownych do obowiązującej wówczas poprawności politycznej.

In this article, the issue of restoring discipline among the diocesan clergy in Galicia is presented, by means of the example of the correctional house in Zagórz. The issue is examined in the context of other Polish territories under Prussian and Russian partition, as well as within the Habsburg monarchy and its subordinate ecclesiastical correctional institutions. This matter is depicted against the backdrop of the prevailing Josephinian and post-Josephinian system of maintaining and restoring discipline among clergy members, not only in terms of moral conduct but also as a means of bringing politically defiant clergy in line with the prevailing political correctness at the time.
Correctional homes for diocesan clergy in the Polish lands in the 19th century with regard to Galicia and the Discalced Carmelite monastery in Zagórze
Keywords: duchowieństwo; nadużycia duchownych; domy emerytów; clergy; clerical misconduct; retirement homes; correctional houses; Zagórz